Performance of Bajomulyo-Pati Coastal Fisheries Port (CFP) on the Regional Economy - Agus Suherman; Abdul Kohar Mudzakir (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
The Coastal Fishery Port (PPP) of Bajomulyo is the largest fishing port in Pati Regency and its existence makes the capture fisheries sector the basis for the economy in Pati Regency. Therefore, this study aims to analyze the activities and performance of CFP Bajomulyo on the regional economy. This was conducted from February to October 2021 at the port. Data analysis was carried out using two methods. The first is the descriptive method which involves analyzing operational activities and assessing operational performance based on the Decision of the Director-General of Capture Fisheries in 2015 Number 20/KEP-DJPT/2015. The second is the Structural Equation Model (SEM) which was used to analyze the determinants of Bajomulyo's CFP performance on the regional economy. The results showed that the port operational activities such as production, value, and ship visits were volatile for the results of the performance assessment based on the guidelines set by the Director-General of Capture Fisheries in 2015. This shows that the operational performance of CFP Bajomulyo from January to September 2020 was successful. Furthermore, the results from the SEM analysis show that the regional economy is influenced by the variables of government policy and CFP performance. Therefore, the good local government policies in the development and management of the port and its performance can improve the regional economy of the Pati Regency.